The effects of combined strength & endurance training - Severino, L.
In most studies the subjects training for strength and endurance performed greater volumes of work than either the strength or endurance only groups. The compromise in strength found by most of the previous studies has been hypothesised by several authors to be due to overtraining. When results of VO2max tests for strength and endurance and endurance only groups were compared, most studies found no significant differences (3, 5, 1, 11), though many also noted that the endurance gains in combination groups were similarly, slightly lower than those of endurance only groups. It has been suggested that if compromises were due to overtraining, that this effect selectively targeted only the adaptations associated with strength(4). It appears that overtraining is not likely the cause of the incompatibility, as it has been pointed out (4) that similar results were obtained with differing total training volumes. One of the studies found, instead of a compromise, that for well trained endurance athletes strength training actually improved their performance (6). This may suggest that interference is limited if strength training is performed only when endurance has been trained to high levels. This may only be of use to athletes who need to attain a high level of endurance for their sport.